Toward community-driven tuberculosis education: findings from a knowledge and engagement pilot survey in the rural community of Eastern Cape, South Africa - Dlatu, Ntandazo; Tsuro, Urgent; Faye, Lindiwe Modest; Hosu, Mojisola Clara, Walter Sisulu University TB Research Group Medical Microbiology 2025 Honours Students; Ncomeka, Sineke; Apalata, Teke (Frontiers in Public Health, 2025)
BackgroundTuberculosis (TB) remains a major public health concern in rural South Africa, with widespread community knowledge gaps and pervasive stigma significantly impeding early diagnosis and treatment success. This pilot study evaluated TB knowledge and barriers to testing among community members in Ntabankulu, Eastern Cape, to inform targeted, community-driven education strategies.MethodsA cross-sectional survey utilizing a structured Knowledge-Attitudes-Practices (KAP-TB) questionnaire was administered to 131 rural community members. TB knowledge was categorized into low, moderate, and high levels based on scores derived from a Likert-type scale. Statistical analysis used Fisher’s exact and Kruskal–Wallis tests to examine associations between knowledge levels, sociodemographic variables, barriers, and TB exposure history. Boxplots provided visual insight into distributions across age and gender.ResultsAmong participants, TB knowledge was mostly moderate (64.9%), with 11.5% reporting low knowledge and 23.7% high knowledge. Knowledge was significantly associated with education level (p < 0.001): 52% of the high-knowledge group had a tertiary education, compared to none in the low-knowledge group. Although gender (p = 0.5) and age (p = 0.2) were not statistically significant overall, boxplot visualization suggested a trend toward higher knowledge scores among younger, male participants, especially those with a history of TB exposure. The most frequently cited barriers to testing were fear of stigma (42%) and lack of knowledge (33%). Low-knowledge participants more frequently reported structural barriers such as distance (10%) and cost (7%). Crucially, participants with a personal (p = 0.047) or family (p < 0.001) history of TB experience were significantly more likely to have high knowledge.ConclusionTB knowledge in this rural setting is primarily shaped by formal education and direct personal experience, while stigma and misinformation remain the predominant barriers to timely testing. Future community-driven education must prioritize leveraging survivor storytelling, peer education, and culturally tailored messaging to simultaneously boost TB literacy, actively reduce stigma, and promote prompt care-seeking.